Pengaruh Return On Investment dan Economic Value Added pada Return Saham Perusahaan Manufaktur - Puspitawati, Lilis; Supardi, Deddy (Jurnal Trikonomika, 2008)
The research aims to estimate the effect of Return On Investment (ROI) and Economic Value Added (EVA) toward stock return and test the Efficient Market Hypothesis semi strong form which are done by manufacture public companies listed in Jakarta Stock Exchange, the samples used 22 manufacture public companies which are include of the three classifications stated: basic industry and chemicals, miscellaneous industry, and consumer good industry. Stating samples used Purposive Sampling. Statistical test used multiple regression to examine the effects of those two variables both partially and simultaneously, to analize the stock return used event study analysis. The results indicate that simultaneously and partially ROI and EVA have positif significant effect toward the stock return. Anathor result indicate ROI have more high correlation toward stock return than EVA. The research indicate that in the reality condition applying EVA in Indonesiaâs capital market have less support. On that account, performance measurement based on EVA ought to be made as of the parameter by company managers as base for invesment in stocks.